Preparation of metal copper organic framework material and application of metal copper organic framework material in preparation of aldehyde through photocatalytic alcohol dehydrogenation
By introducing metal copper into metal organic frame materials and using photocatalytic technology to efficiently oxidize alcohols into aldehydes at room temperature, the problems of high energy consumption and environmental pollution in traditional production methods are solved, and green and efficient aldehyde production is achieved.
Patent Information
- Application Number
- CN202411895338.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-21
AI Technical Summary
Traditional formaldehyde and acetaldehyde production methods have problems of high energy consumption, environmental pollution and many by-products, especially in the presence of high temperatures and oxidants.
A metal organic frame (MOF) supported by metal copper is used as a photocatalyst, and alcohol compounds are highly selectively oxidized to the corresponding aldehydes by light through room temperature and normal pressure.
It has achieved efficient oxidation of alcohol compounds into aldehydes under mild conditions, which significantly reduces energy consumption and reduces the generation of by-products, and has the advantage of green and environmental protection.
Smart Images

Figure CN119680648A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalysis, and specifically relates to the preparation of a metal copper organic framework material and the application of the material in photocatalytic alcohol dehydrogenation to produce aldehydes. Background Art
[0002] Formaldehyde is an important chemical raw material, which plays an irreplaceable role in industries such as plastics, coatings, pharmaceuticals and textiles. With the development of industrialization and urbanization, the demand for formaldehyde and its derivatives continues to grow, which has promoted the research and optimization of formaldehyde production technology. At present, the production of formaldehyde mainly uses methanol as raw material, and methanol is oxidized to produce formaldehyde using a catalyst in an oxygen atmosphere. Since methanol oxidation is an exothermic reaction, methanol oxidation is usually carried out at above 600°C. In addition, formaldehyde is also a substance that is easily oxidized, and the reaction is carried out in an oxidizing atmosphere in the presence of O2, which easily causes formaldehyde to be over-oxidized to produce by-products such as formic acid, carbon monoxide and carbon dioxide. In general, the current traditional method of producing formaldehyde has problems such as high energy consumption and many by-products. It is not only costly, but also easy to cause environmental pollution. Therefore, it is very meaningful to develop a new path to achieve a method of producing formaldehyde by methanol oxidation under mild conditions without the use of strong oxidants.
[0003] Acetaldehyde is also an important chemical raw material, which is widely used in industries such as plastics, fragrances, medicines and dyes. With the continuous expansion of industrialization and consumer markets, the demand for acetaldehyde and its derivatives is also growing, which has promoted the research and innovation of acetaldehyde production technology. At present, the production of acetaldehyde mainly uses ethanol as raw material, and acetaldehyde is prepared by catalytic oxidation under high temperature conditions. However, due to the high temperature requirement of ethanol oxidation reaction (usually above 300°C), the energy consumption is large. In addition, acetaldehyde is easily further oxidized to acetic acid or completely decomposed into carbon dioxide and water, resulting in the formation of more by-products, reducing product selectivity and economy, and also increasing the environmental burden. Therefore, it is very meaningful to develop a new route to realize the method of ethanol oxidation to acetaldehyde under mild conditions using photocatalytic technology. Photocatalytic reaction uses sunlight or artificial light as energy source, does not require strong oxidants, can react at room temperature, significantly reduces energy consumption, and by designing a suitable catalyst system, it is expected to improve the selectivity of acetaldehyde and reduce the formation of by-products.
[0004] In summary, the photocatalytic oxidation of methanol to formaldehyde and ethanol to acetaldehyde can not only effectively reduce the energy consumption and environmental pollution of the production process, but also significantly improve the reaction selectivity and reduce the generation of by-products. This method of direct photocatalytic conversion of alcohols into aldehydes has the advantages of being green, efficient and sustainable, and has important research significance and application prospects for modern chemical production. Summary of the invention
[0005] The present invention aims to solve the problems of high energy consumption, environmental pollution, and the use of strong oxidants in the production of traditional industrial aldehydes, and provides a method for preparing a metal copper organic framework material and its application in photocatalytic alcohol dehydrogenation to produce aldehydes. The present invention uses a metal organic framework (MOF) loaded with metal copper as a photocatalyst to selectively oxidize alcohol compounds to corresponding aldehydes through light. The process can occur at room temperature and pressure without the need for an oxidant, and has the advantages of being greener and more environmentally friendly.
[0006] The method for preparing the metal copper organic framework material of the present invention comprises the following steps:
[0007] Step 1: Add tetrabutyl titanate and 1,4-phthalic acid into a mixed solvent consisting of anhydrous N,N-dimethylformamide (DMF) and anhydrous methanol, and disperse them evenly by ultrasonication; heat the resulting mixture in a 20 mL high-pressure reactor, cool to room temperature, collect the product by centrifugation, wash it three times with anhydrous DMF and anhydrous methanol respectively, dry the collected solid under vacuum, and activate it under vacuum to obtain MIL-125.
[0008] Step 2: Ultrasonic dispersion of the MIL-125(Ti) obtained in step 1 in methanol was performed uniformly, and the mixture was transferred to a photocatalytic quartz reactor. The reactor was then filled with an inert gas, and a xenon lamp was used to irradiate the reactor for a period of time, and then the irradiation was stopped and different concentrations of CuCl2 solutions were injected. After stirring, the mixture was transferred to a centrifuge tube for centrifugal separation, and the product Cu was obtained after drying. X -MIL-125.
[0009] In step 1, the temperature of the heating reaction in the high-pressure reactor is 130° C., the reaction time is 15 h, and the heating rate is 2-8° C. / min.
[0010] In step 2, the reactor was irradiated with a 300 W xenon lamp for 0.5 h, then the irradiation was stopped and different concentrations of CuCl2 solutions were injected. After stirring, the mixture was transferred to a centrifuge tube and centrifuged. After drying, the product Cu X -MIL-125.
[0011] The present invention introduces copper (Cu) with different metal loadings into the metal organic framework material (MIL-125), denoted as Cu x -MIL-125 (x = 0, 0.8, 1.6, 2.0), using MIL-125 to produce an intermediate state with high reducibility under light conditions to achieve the reduction loading of Cu and avoid the use of reducing agents.
[0012] Furthermore, the amount of Cu loaded on the MOF material can be controlled by controlling the amount of precursor added, x=0.8-2.0, preferably x=0.8-1.6.
[0013] The invention discloses an application of the metal copper organic framework material in photocatalytic dehydrogenation of alcohol compounds to produce aldehydes.
[0014] The alcohol compounds include methanol, ethanol and the like.
[0015] The 10 mg Cu X -MIL-125 material (x=0.8-1.6) was placed in 10 mL of anhydrous alcohol compound and dispersed evenly by ultrasonication. The mixture was transferred to a photocatalytic quartz reactor, and an inert gas was filled into the reactor. The reactor was irradiated with a 300 W xenon lamp for 2 h, and the gas phase product was detected by gas chromatography, and the liquid phase product was quantitatively detected by nuclear magnetic resonance.
[0016] There are several traditional methods for introducing metals into Ti-MOF: 1. Doping method: During the synthesis of Ti-MOF, the precursors of other metals (such as Zn 2+ , Fe 3+ , Cu 2+ 1. The method of adding metals to the MOF is to form multi-metal nodes or mixed metal clusters. The addition of metals during the synthesis stage will cause the crystal structure of MOF to be unstable. 2. Impregnation method: The synthesized Ti-MOF is immersed in a solution containing the target metal, and the metal is loaded into the MOF structure through the combination of the metal and the coordination site (such as carboxylic acid group, hydroxyl group) in the framework. However, this method will cause uneven distribution of metal ions and limited loading. 3. Vapor deposition method: The metal atomic layer is precisely deposited on the surface or inside of Ti-MOF through chemical vapor deposition technology. Although highly uniform metal distribution can be achieved, the equipment requirements are high and expensive. 4. Reduction method: Ti-MOF is immersed in a metal salt solution, and then the metal is reduced to nanoparticles loaded on the surface or pores of MOF by a reducing agent (such as NaBH4) or heat treatment, but pyrolysis may destroy the unique pore structure of MOF and reduce the catalytic activity.
[0017] The present invention introduces Cu metal into the synthesized MIL-125 (Ti) to obtain a catalytic material. This is different from the doping method that introduces metal in the synthesis stage, so the MOF material retains the overall structure and does not destroy its crystallinity. In addition, the present invention utilizes MIL-125 to generate intermediate species with high reducing ability after light exposure, thereby exposing unsaturated coordination sites at specific positions, so the position of metal anchoring can be precisely controlled, and the process of anchoring the metal does not require high-temperature treatment and is low in price.
[0018] In addition, the metal copper organic framework material of the present invention can not only smoothly realize the photocatalytic dehydrogenation of methanol to formaldehyde, but also realize the photocatalytic dehydrogenation of ethanol to acetaldehyde. Those skilled in the art know that ethanol is more difficult to dehydrogenate than methanol. On the one hand, from the perspective of thermal catalysis, ethanol is more stable than methanol because the bond energy of the CH bond in ethanol is higher; furthermore, the activation energy of the ethanol dehydrogenation reaction is also higher than that of methanol. On the other hand, from the perspective of photocatalysis, the photocatalytic reaction requires the effective separation and transfer of electron-hole pairs. The smaller molecular size and simple electronic structure of methanol may be more suitable for the energy level matching of the photocatalyst. The complex structure of ethanol may lead to a longer electron transfer path or unsatisfactory energy matching, thereby reducing the photocatalytic efficiency.
[0019] The reason why the metal copper organic framework material of the present invention can simultaneously realize the photocatalytic dehydrogenation of methanol and ethanol to formaldehyde and acetaldehyde is:
[0020] First, the conduction band (CB) and valence band (VB) energy structures of the catalysts have sufficient driving force for the dehydrogenation of methanol and ethanol: the conduction band electrons can participate in the reduction reaction (e.g., reducing H + The holes in the valence band have sufficient oxidizing power to effectively extract electrons from methanol and ethanol molecules and initiate the dehydrogenation reaction.
[0021] Secondly, Ti-MOF catalysts can generally absorb a wide range of light (including ultraviolet light, visible light and even near-infrared light), which can provide sufficient photogenerated electrons and holes for different reactions: for methanol and ethanol, the energy requirements may be different, but the photocatalyst can generate enough electron-hole pairs to meet the activation requirements of the two molecules through effective light absorption. In addition, the rational doping of Cu in the present invention changes the band gap structure of the catalyst and improves the utilization rate of visible light.
[0022] Taking ethanol as an example, in the photocatalytic reaction process of the metal copper organic framework material of the present invention, light is irradiated to the Ti-based catalyst to generate electron-hole pairs, and ethanol is adsorbed to the Cu active site at the same time. Then the photogenerated holes attack the α-CH of ethanol, and ethanol loses an H atom to generate an intermediate ethoxy group adsorbed on the Cu active site. The intermediate ethoxy group further loses the H atom on the hydroxyl group on Cu to generate acetaldehyde, and the two lost protons obtain photogenerated electrons to obtain H2.
[0023] The present invention proves that the catalyst will not be deactivated through cyclic experiments. First, photocatalysis is different from thermal catalysis and belongs to mild conditions, so it is not easy to cause thermal aggregation to destroy the structure of the catalyst. Secondly, since the position of the metal can be accurately controlled, the Cu atoms and the O on the Ti-O cluster are accurately coordinated to form a stable structure to ensure the stable catalytic reaction.
[0024] The beneficial effects of the present invention are embodied in:
[0025] 1. The present invention is a metal organic framework material based on MIL-125, which has the characteristics of rich pore size, low density, etc. and has good industrial application prospects.
[0026] 2. The present invention utilizes MIL-125 to generate intermediate species with high reducing ability after illumination to achieve the reduction of metals. Unlike the traditional impregnation-reduction method, it does not require the use of reducing agents such as H2.
[0027] 3. The present invention uses light to selectively oxidize alcohol compounds into corresponding aldehyde compounds. This process can occur at room temperature and normal pressure without the use of oxidants. Compared with traditional industrial methods, it has the advantages of being greener and more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The Cu prepared by introducing metal into the metal organic framework structure of the present invention X -PXRD of MIL-125 catalyst material.
[0029] Figure 2 The Cu prepared by introducing metal into the metal organic framework structure of the present invention X -SEM image of MIL-125 catalyst material.
[0030] Figure 3 The Cu prepared by introducing metal into the metal organic framework structure of the present invention X -MIL-125 catalyst material is used for UV-Vis spectrophotometry.
[0031] Figure 4 The Cu prepared by introducing metal into the metal organic framework structure of the present invention X -Selectivity diagram of liquid products in the dehydrogenation of methanol to formaldehyde using MIL-125 catalyst material.
[0032] Figure 5 The Cu prepared by introducing metal into the metal organic framework structure of the present invention X - Cycle diagram of the MIL-125 catalyst material for the dehydrogenation of methanol to formaldehyde.
[0033] Figure 6 The Cu prepared by introducing metal into the metal organic framework structure of the present invention X - Cycle diagram of the MIL-125 catalyst material for the dehydrogenation of ethanol to acetaldehyde. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further analyzed and explained below through specific embodiments.
[0035] Example 1: Composite material based on the introduction of metal into a metal organic framework structure
[0036] 1. Preparation method
[0037] 1. Preparation of MIL-125
[0038] 0.3 mL of tetrabutyl titanate and 0.6 g of 1,4-phthalic acid were added to 9 mL of anhydrous N,N-dimethylformamide (DMF) and 1.2 mL of anhydrous methanol and ultrasonically dispersed uniformly. The resulting mixture was placed in a 20 mL high-pressure reactor and heated at 130 °C for 15 h. After cooling to room temperature, the product was collected by centrifugation and washed three times with anhydrous DMF and anhydrous methanol respectively. The collected solid was vacuum activated at 120 °C to obtain MIL-125 for use.
[0039] 2. Cu at specific metal anchoring sites X -Preparation of MIL-125 catalyst material
[0040] 20 mg of purified MIL-125 material was accurately weighed and placed in 10 mL of anhydrous methanol solution. Ultrasonic instruments were used to fully disperse the material to ensure that the material was evenly dispersed in the methanol solution to form a uniform mixed solution. During the dispersion process, the sample can be placed in an ice bath to avoid long-term ultrasound causing the solution to heat up.
[0041] Next, the evenly dispersed mixed liquid is carefully transferred to a photocatalytic quartz reactor for photocatalytic reaction. In the reactor, high-purity inert gas (such as nitrogen or argon) is filled to remove oxygen or other impurity gases in the reactor to ensure that the reaction system is in a completely inert environment. Subsequently, a 300W xenon lamp is used as a light source to illuminate the mixture in the reactor, and the illumination time is set to 0.5 hours. During this process, the light energy provided by the xenon lamp can excite the MIL-125 material, prompting it to produce intermediate species with high reducibility, thereby preparing for the subsequent introduction of metal ions.
[0042] After the irradiation is completed, the light source is stopped, and different concentrations of CuCl2 solution are injected into the reaction system according to the experimental design. In order to ensure that the CuCl2 solution is fully in contact with the MIL-125 material, magnetic stirring is performed quickly so that the copper ions in the solution can be effectively adsorbed into the framework structure of MIL-125 and reduced.
[0043] Subsequently, the stirred mixed liquid is transferred from the reactor to a centrifuge tube and centrifuged using a high-speed centrifuge to ensure that the solid product and the supernatant are completely separated. The separated solid product is washed multiple times with anhydrous solvent to remove excess copper ions and residual solvent adsorbed on the surface of the material.
[0044] Finally, the separated solid product is dried at low temperature (usually dried in a vacuum drying oven at 60-80°C for several hours) to obtain the target product Cu doped with copper ions. X -MIL-125. After drying, the product can be collected and sealed for storage for further photocatalytic performance research or structural characterization analysis.
[0045] 2. Testing
[0046] 1. The obtained Cu with different loadings X -MIL-125 was characterized by PXRD, the results are as follows Figure 1 As shown. Figure 1 It can be seen that the Cu X -MIL-125 crystal form remains intact, proving that the Cu prepared by the present invention X -MIL-125 material is structurally correct and the crystal structure is not disrupted after anchoring the metal.
[0047] 2. The obtained Cu with different loadings X -MIL-125 was subjected to ICP to determine the metal loading, and the results are shown in Table 1. Table 1 shows the Cu prepared by introducing metal into the metal organic framework structure of the present invention. X - ICP results of MIL-125 catalyst material. As shown in Table 1, by adjusting the concentration of different CuCl2 solution precursors, the loading of Cu can be accurately adjusted, which proves that the Cu prepared by the present invention X -MIL-125 material has the characteristics of precise and adjustable metal loading.
[0048]
[0049] 3. The obtained Cu with different loadings X -MIL-125 was characterized by scanning electron microscopy. Figure 2 As shown. Figure 2 It can be seen that the morphology of the MOF of the present invention can still be maintained after the introduction of Cu metal.
[0050] 4. The obtained Cu with different loadings X -MIL-125 was characterized by UV-Vis spectrophotometry, and the results were as follows Figure 3 As shown. Figure 3 It can be seen that the material has good potential for solar energy utilization, proving that the Cu prepared by the present invention X -MIL-125 material has the characteristics that can be applied to photocatalytic reactions.
[0051] 5. The obtained Cu with different loadings X -MIL-125 was used to detect the gas phase products of methanol dehydrogenation to formaldehyde by GC and the liquid phase products by NMR or UV-visible spectrophotometry. The results are shown in Table 2. As can be seen from Table 2, under nitrogen atmosphere, different loadings of Cu X -MIL-125 was used as the catalyst, and the solvent was methanol or ethanol. After 2 h of light reaction, the H2 yield was monitored by GC, and the formaldehyde or acetaldehyde yield was detected by NMR or UV-visible spectrophotometry. The results showed that: 1. After anchoring the metal Cu, the activity of methanol dehydrogenation to formaldehyde or ethanol dehydrogenation to acetaldehyde was greatly improved compared with the original MIL-125 (Ti). 2. With the increase of Cu loading, the reaction activity showed a volcano-shaped curve, and the activity was the highest when the loading was 1.6%.
[0052] 6. The highest activity Cu 1.6 -MIL-125 detects the yield of aldehyde compounds by NMR or UV-visible spectrophotometry. The results are as follows Figure 4 As shown. Figure 4 As shown in the figure, the catalyst still maintains good activity and selectivity after the third cycle experiment. X -MIL-125 material can be recycled as a catalyst for the dehydrogenation of alcohols to produce aldehydes.
[0053] Example 2: Application of the MOF material prepared by the present invention in the dehydrogenation of alcohols to produce aldehydes
[0054] 1. Effect of different Cu loading on catalysts
[0055] Method: Take Cu X -MIL-125 catalyst material 10 mg, anhydrous methanol or anhydrous ethanol 10 mL were added to a 160 mL photocatalytic quartz reactor, and irradiated with a 300 W xenon lamp for 2 h. Hydrogen was checked by gas chromatography, and formaldehyde was detected by nuclear magnetic resonance. The reaction formula is as follows.
[0056]
[0057] Table 2 is the Cu prepared by introducing metal into the metal organic framework structure of the present invention. X -Product activity of methanol dehydrogenation to formaldehyde reaction of MIL-125 catalyst material.
[0058]
[0059] Table 3 is the Cu prepared by introducing metal into the metal organic framework structure of the present invention. X-Product activity of MIL-125 catalyst material in the dehydrogenation of ethanol to acetaldehyde.
[0060]
[0061] The reason why the reaction activity presents a volcano-shaped curve may be that metals usually play a role in capturing electrons or promoting electron-hole separation in photocatalysis. However, if the metal loading is too high, the excess metal sites will become the recombination centers of electron-hole pairs, leading to the rapid recombination of photogenerated carriers, thus significantly reducing the photocatalytic performance.
[0062] 2. Recyclability of catalyst
[0063] Catalyst recovery: After the reaction is completed, filter to separate the catalyst from the reaction mixture, filter out, and dry.
[0064] Specific operation of the cycle experiment: Take the most active Cu 1.6 -MIL-125 catalyst material 10 mg and anhydrous methanol 10 mL were added into a 160 mL photocatalytic quartz reactor respectively. After irradiation with a 300 W xenon lamp for 2 h, the H2 yield was detected by GC, and the formaldehyde or acetaldehyde yield was detected by nuclear magnetic resonance or UV-visible spectrophotometry.
[0065] like Figure 5 and Figure 6 As shown in the figure, the catalyst still maintains good activity and selectivity after the third cycle experiment. X -MIL-125 catalyst material can be recycled as a catalyst for the dehydrogenation of alcohols to produce aldehydes.
Claims
1. A method for preparing a metal copper organic framework material, characterized in that The steps include: Step 1: Tetrabutyl titanate and 1,4-phthalic acid are added to a mixed solvent consisting of anhydrous N,N-dimethylformamide and anhydrous methanol, and ultrasonically dispersed uniformly; the obtained mixture is placed in a high-pressure reactor for heating, and after cooling to room temperature, the product is collected by centrifugation, washed with anhydrous DMF and anhydrous methanol respectively, and the collected solid is dried under vacuum and vacuum activated to obtain MIL-125 (Ti); Step 2: Ultrasonic dispersion of the MIL-125(Ti) obtained in step 1 in methanol was performed uniformly, and the mixture was transferred to a photocatalytic quartz reactor. The reactor was then filled with an inert gas, and a xenon lamp was used to irradiate the reactor for a period of time, and then the irradiation was stopped and different concentrations of CuCl2 solutions were injected. After stirring, the mixture was transferred to a centrifuge tube for centrifugal separation, and the product Cu was obtained after drying. X -MIL-125.
2. The preparation method according to claim 1, characterized in that: In step 1, the temperature of the heating reaction in the high-pressure reactor is 130° C., the reaction time is 15 h, and the heating rate is 2-8° C. / min.
3. The preparation method according to claim 1, characterized in that: In step 2, the reactor was irradiated with a 300 W xenon lamp for 0.5 h, then the illumination was stopped and CuCl2 solutions of different concentrations were injected. The Cu loading amount was controlled by controlling the amount of precursor CuCl2 added.
4. The preparation method according to claim 3, characterized in that: The Cu loading is 0.8%-2.0%.
5. The preparation method according to claim 3, characterized in that: The Cu loading is 0.8%-1.6%.
6. Use of the metallic copper organic framework material prepared by the preparation method according to any one of claims 1 to 5 in photocatalytic dehydrogenation of alcohol compounds to produce aldehydes.
7. The use according to claim 6, characterized in that: The alcohol compound includes one or more of methanol and ethanol.
8. The use according to claim 6 or 7, characterized in that: The metal copper organic framework material Cu X -MIL-125 is placed in anhydrous alcohol compounds and dispersed evenly by ultrasonication. The mixture is transferred to a photocatalytic quartz reactor, an inert gas is filled into the reactor, and a xenon lamp is used to irradiate the reactor for photocatalytic dehydrogenation reaction.
Citation Information
Patent Citations
Preparation and application of Cu-NM-101(Fe) photocatalyst
CN113231101A
Copper-based MOF photocatalyst, preparation method and application
CN118142587A
Titanium-containing metal organic framework material as well as preparation method and application thereof
CN118440336A
Cu / NH2-MIL-125 (Ti) photocatalyst as well as preparation method and application thereof
CN118454734A
Manufacturing method of hydrogen from methanol using light catalyst
KR1020150000007A